Determination of the angles of pressure in the system of limitation by optimisation of linkages - Demokritova, Alexandra; Demokritov, Vladimir (Transport, 2006)
In the present paper a method of analytical determination of reactions and angles of pressure is considered with the four-bar linkage as an example. The determined sequence for the expression of acceleration of the points and angle acceleration of the links is presented. Further the power analysis for Assur’s group is made. The equations of normal components of reactions are expressed as straight lines passing across given point in the given direction. The equations of the full reactions in the hinges are expressed as straight lines passing across two given points. After that the angles of pressure are expressed as the angles between directions of the speed and reactions.First Published Online: 27 Oct 2010